Invisible men: mobility and political change on the frontier of late Roman Africa. Issue 3 (2nd July 2018) - Merrills, Andy
Abstract : The political hierarchies that developed in North Africa in the post‐Roman period have traditionally been ascribed either to invading groups from the Sahara, or to indigenous elites who transformed their political authority to respond to changing circumstances. The present article suggests that such interpretations have neglected the role played by seasonal pastoralists within the emergence of these new polities. Human mobility was a crucial feature of the late antique Maghreb, as analysis of the later Roman frontier system reveals. Equally, contemporary anthropological scholarship emphasizes the influence that mobile groups can have in periods of social and political upheaval and their capacity for hierarchical stratification. The article offers two brief case studies, and argues that Antalas, leader of the 'Frexes' in southern Byzacena, and the occupants of the 'Djedar' tumulus mausolea near Tiaret, are best viewed as products of a mobile society.